22 Enhancing medical training: improving morale, training, and working lives for doctors in training in oxford. (12th November 2018) - FitzPatrick, Michael; Cargill, Tamsin; Martin, Judy; Capel, Ifor
Abstract : Physician engagement and burnout are major workforce issues in healthcare. Morale and engagement of junior doctors is low, with increasing numbers taking time out of training, or leaving the profession. There is widespread dissatisfaction with current training paradigms in post-graduate medical education. In 2016, we conducted a survey of the working lives of junior doctors at Oxford University Hospitals. The responses of 146 junior doctors highlighted areas for improvement in induction, working lives, and training. Doctors reported significant rates of presenteeism (53%) and burnout (62%). Results were presented to organisational leaders, educators, and junior doctor forums. These meetings acted as a spur for change, and led to the development of a bespoke engagement event. We conceived and designed a one-day engagement workshop to explore junior doctors' morale, training, and working lives. Over 40 junior doctors and consultants joined patient representatives and organisation leaders for the event. This consisted of 3 workshops, followed by a competition to develop trainee-led improvement projects. The first workshop explored the lived experiences of junior doctors' working lives. The second discussed how healthcare demands and the medical profession will change by 2030, and how medical training will need to change to meet these future demands. The third workshop discussed the interventions needed to achieve excellence in medical training, and agreed a preliminary timeline for this improvement. The results of the event informed a strategy for enhancing post-graduate medical training, and highlighted several areas for immediate improvement. The outcomes of this meeting were discussed at junior doctor forums, the medical director's office, HR department, education department, and regional education committees, at which feedback was sought. This work provides a co-produced vision of excellence in physician training and working lives which we can strive to achieve.